Agriculture, Environment and Development: International Perspectives on Water, Land and Politics, Second Edition - Ioris, Antonio Augusto Rossotto; Fernandes, Bernardo Mançano [UNESP] (Springer Nature, 2022)
The Second Edition of this book is completely revised and updated throughout providing an overview of current challenges faced within the area of Agri-food in relation to policymaking, ecological conservation and socio-environmental justice. Including a range of new chapters, the book explores some of the conceptual and analytical gaps that are presented by current approaches to this topic. The series of interconnected chapters offers a critical reinterpretation of the tensions associated with the failures of mainstream regulatory regimes, land and resource grabbing, and the impacts of global agri-food chains at local, regional and inter-sectoral scales. The book also examines past legacies and emerging challenges associated with agriculture modernisation, politico-spatial disputes, climate change, social movements, gender, ethnicity and education. It likewise addresses the transformative potential of different combinations of biophysical, socio-technical and socio-spatial practices of food sovereignty.